2021
DOI: 10.1111/codi.15698
|View full text |Cite
|
Sign up to set email alerts
|

The role of intraoperative radiotherapy in advanced rectal cancer: a meta‐analysis

Abstract: Locally advanced and locally recurrent rectal cancers (LARC/ LRRC) represent two distinct clinical entities, yet they pose the single greatest challenge to colorectal surgeons, namely obtaining a negative resection margin in the presence of complex, advanced disease. Neoadjuvant radiotherapy can facilitate downstaging of advanced tumours, and improved local control is well documented [1][2][3][4]. Unfortunately, a proportion of patients will have threatened margins making a complete resection (R0) difficult. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Most of the challenges in the treatment of rectal cancer concern the lowest located and the locally advanced tumors. Several reports have described the availability and effectiveness of IOeRT combined with preoperative chemoradiation for controlling LARC [ 12 ] and promoting improved local control results compared to non-IOeRT strategies based on systematic reviews [ 13 , 14 ]. In particular, the data reported in cT4 patients and isolated recurrences, using IOeRT as a component of local intensification treatments [ 15 , 16 ], are incorporated in the experts’ guidelines as a component of the multimodal treatment that is recommended in clinical practice [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the challenges in the treatment of rectal cancer concern the lowest located and the locally advanced tumors. Several reports have described the availability and effectiveness of IOeRT combined with preoperative chemoradiation for controlling LARC [ 12 ] and promoting improved local control results compared to non-IOeRT strategies based on systematic reviews [ 13 , 14 ]. In particular, the data reported in cT4 patients and isolated recurrences, using IOeRT as a component of local intensification treatments [ 15 , 16 ], are incorporated in the experts’ guidelines as a component of the multimodal treatment that is recommended in clinical practice [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…They reported a nonsignificant decrease in locoregional recurrence (14.7% vs. 21.4%, P = 0.11), with no significant increase in overall complication rate (36.3% vs. 28.6%) with IORT. 50 Mirnezami et al found a higher rate of postoperative wound complications with IORT, although no differences in ureter injury or anastomotic complications were detected. 48…”
Section: Intraoperative Radiation Therapymentioning
confidence: 96%
“…A similarly designed meta-analysis by Fahy et al included many of the same studies, with over 800 patients with locally advanced or recurrent rectal cancer treated with IORT versus surgery/EBRT. They reported a nonsignificant decrease in locoregional recurrence (14.7% vs. 21.4%, P = 0.11), with no significant increase in overall complication rate (36.3% vs. 28.6%) with IORT 50 . Mirnezami et al found a higher rate of postoperative wound complications with IORT, although no differences in ureter injury or anastomotic complications were detected 48 …”
Section: Principles Of Radiation Therapymentioning
confidence: 97%
“…Fahy et al from Ireland published a meta-analysis in 2021 examining the role of IORT as part of the multimodality treatment of both locally advanced and locally recurrent rectal cancers. 22 They included patients treated from 2000 to 2020 treated with surgery/EBRT with or without IORT with a primary endpoint of LR. Seven papers met the criteria for inclusion.…”
Section: Iort Processmentioning
confidence: 99%